Customer Satisfaction Through Service Speed and Compliance - Dolly Senja Permadi; Wahib Gunadi (Arthatama: Journal of Business Management and Accounting, 2025)
This study investigates the strategic balance between service speed and operational compliance in influencing customer satisfaction at BRI Branch Office A Rifai. The conflict arises when marketing units prioritize rapid service to meet business targets, while operational units strictly enforce standard operating procedures (SOPs), creating internal tension. Adopting a qualitative research method, data were collected through in-depth interviews, field observations, and internal document analysis to explore integrative solutions that address both needs. The findings indicate that fast services without proper document verification increase the risks of operational errors, legal violations, and reputational damage. On the other hand, overly rigid procedures reduce customer satisfaction. To mitigate these issues, this study recommends adaptive strategies such as the "buying time" approach, SOP redesign, and enhanced cross-functional collaboration. This research contributes to service management theory in the digital banking landscape and provides practical guidance for designing scalable service models that align institutional compliance with customer expectations.